Add-on quetiapine in the treatment of major depressive disorder in elderly patients with cerebrovascular damage - Carta, Mauro Giovanni (BioMed Central, 2007)
BACKGROUND: Depressive episodes in elderly patients with cerebrovascular damage are characterized by poor responses to standard antidepressants. Recent reports have suggested that the atypical antipsychotic, quetiapine may have antidepressant properties and, in mice, may prevents memory impairment and hippocampus neurodegeneration induced by global cerebral ischemia. OBJECTIVE: To evaluate the efficacy of combination therapy with quetiapine in depressed elderly patients with cerebrovascular damage. METHODS: An open-label, 6-month follow-up study of patients with major depressive disorder (DSM-IV) and cerebral abnormalities (assessed by MRI) without severe cognitive impairment. Patients who had not responded to standard antidepressants (months of treatment 6.5 ± 7.2) additionally received quetiapine (300 ± 111 mg/d). Patients were evaluated at baseline (t0) and Months 1, 3, and 6 (t1, t3, t6) using the Clinical Global Impressions Scale for Severity (CGI-S) and the Hamilton Depression Rating Scale (HAM-D). RESULTS: Nine patients were included in the study, with a mean age of 72.8 ± 9.4 years. CGI-S scores decreased from baseline to Month 6: 5.8 ± 0.7 (t0), 5.4 ± 0.7 (t1), 5.0 ± 0.8 (t3), and 4.5 ± 1.0 (t6), with a significant improvement at 6 months compared with baseline (P = 0.006). A significant improvement over the 6-month period was also observed with HAM-D scores (t0 = 27.2 ± 4.0, t6 = 14.8 ± 3.8, P < 0.001). CONCLUSION: In this study, quetiapine was efficacious as combination therapy in depressed elderly patients with cerebrovascular damage. The promising results from this study warrant confirmation in large, randomized, double-blind, placebo-controlled studies.